2012
DOI: 10.1016/j.curtheres.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraoperative Paracetamol on Catheter-Related Bladder Discomfort: A Prospective, Randomized, Double-Blind Study

Abstract: Intraoperative single-dose paracetamol was found to be effective in reducing the severity of CRBD and pain in urologic surgery. We suggest that it may be an efficient, reliable, easy-to-apply drug for CRBD. ClinicalTrials.gov identifier: NCT01652183.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 22 publications
1
63
0
1
Order By: Relevance
“…The absolute risk reductions in the experimental group compared with the control group at 6 hours after surgery were 28% to 59% for TURBT (pooled RR: 0.55, 95% CI: 0.31, 0.99, p = 0.04), 4,5 39% to 59% for PNCL (pooled RR: 0.51, 95% CI: 0.37, 0.70, p < 0.001), 3,12,13 and 66% to 67% for nonurological surgery (pooled RR: 0.26, 95% CI: 0.11, 0.59, p = 0.001). Obviously, the effectiveness of the intervention at 6 hours after TURBT was lesser than nonurological surgery.…”
Section: Search Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The absolute risk reductions in the experimental group compared with the control group at 6 hours after surgery were 28% to 59% for TURBT (pooled RR: 0.55, 95% CI: 0.31, 0.99, p = 0.04), 4,5 39% to 59% for PNCL (pooled RR: 0.51, 95% CI: 0.37, 0.70, p < 0.001), 3,12,13 and 66% to 67% for nonurological surgery (pooled RR: 0.26, 95% CI: 0.11, 0.59, p = 0.001). Obviously, the effectiveness of the intervention at 6 hours after TURBT was lesser than nonurological surgery.…”
Section: Search Resultsmentioning
confidence: 97%
“…Paracetamol: Ergenoglu et al 13 found that a single intraoperative dose of i.v. paracetamol (15 mg/kg) decreased the severity of CRBD and total meperidine administration.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations